Analisis Identifikasi Bahaya Kecelakaan Kerja Menggunakan Metode Job Safety Analysis (JSA) dengan Pendekatan Hazard Identification, Risk Assessment And Risk Control (HIRARC) di Departemen Stamping Studi Kasus: PT. Mitra Metal Perkasa - Tata Sulaeman; Ferida Yuamita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Occupational Health and Safety (OHS) is an important aspect of the manufacturing industry to prevent workplace accidents and create a safe working environment. The Stamping Department of PT Mitra Metal Perkasa involves various work activities with potential hazards, such as material loading on coiler machines, stamping processes, welding activities, and material handling. Based on workplace accident data from 2023–2026, approximately 8 accident cases occurred, including hand injuries caused by machine entrapment, material rebounds, cuts from metal scraps, and ergonomic risks. Therefore, hazard identification and risk assessment are required to minimize the potential for workplace accidents.This study aims to identify potential hazards, assess occupational accident risks, and propose risk control measures in the Stamping Department of PT Mitra Metal Perkasa. The method used is Job Safety Analysis (JSA) with the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach. Data were collected through observation, interviews, documentation, and company accident records. The expected results of this study are the identification of hazards in each work activity, determination of risk levels based on low, moderate, high, and extreme risk categories, and recommendations for risk control based on the hierarchy of hazard controls.